2015
DOI: 10.1242/dmm.017699
|View full text |Cite
|
Sign up to set email alerts
|

Cell-based therapies for experimental chronic kidney disease: a systematic review and meta-analysis

Abstract: Cell-based therapy is a promising strategy for treating chronic kidney disease (CKD) and is currently the focus of preclinical studies. We performed a systematic review and meta-analysis to evaluate the efficacy of cell-based therapy in preclinical (animal) studies of CKD, and determined factors affecting cell-based therapy efficacy in order to guide future clinical trials. In total, 71 articles met the inclusion criteria. Standardised mean differences (SMD) and 95% confidence intervals (CI) were calculated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
103
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(106 citation statements)
references
References 91 publications
2
103
0
1
Order By: Relevance
“…Chronic diabetic kidney disease is characterized by a reduced renal regenerative capacity [13] , which is modulated by inflammation [14] . The link between inflammation and regeneration is the sharing of signaling pathways that regulate cell death cell cycle control.…”
Section: Role Of Proximal Tubular Epithelial Cellsmentioning
confidence: 99%
“…Chronic diabetic kidney disease is characterized by a reduced renal regenerative capacity [13] , which is modulated by inflammation [14] . The link between inflammation and regeneration is the sharing of signaling pathways that regulate cell death cell cycle control.…”
Section: Role Of Proximal Tubular Epithelial Cellsmentioning
confidence: 99%
“…However, direct evidence from glomerulosclerosis and interstitial fibrosis analyses was incomplete. Additionally, Li et al 24 found that human MSCs prevented hyperglycemia-induced podocyte apoptosis and injury, and other investigations have shown that in animal models of diabetic nephropathy, MSCs reduced glomerulosclerosis and oxidative stress 18, 20, 25, 26 . We also previously demonstrated the beneficial effect of EPC and MSC transplantation in a porcine model of renovascular hypertension, wherein intrarenal delivery of cells attenuated renovascular hypertension-induced myocardial injury and decreased renal injury 19, 27, 28 …”
Section: Introductionmentioning
confidence: 96%
“…In a systematic review and meta-analysis of 71 articles in animal models, Papazova et al 20 found that cell-based therapy reduced development and progression of CKD. This was evidenced by decreases in urinary protein and urea, which structurally associated with glomerulosclerosis and interstitial fibrosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of the effect of stem cells on chronic kidney disease (CKD) showed beneficial effect, which might give hope to ESRD cases, as the CKD in the study had various grades and some of them represent chronic renal failure. 3 In the beginning of stem cell therapy, it was postulated that the stem cells would home to the damaged area and differentiate into the needed cells to replace the damaged cells. However, most tracing studies showed that most of the stem cells did not replace the damaged cells.…”
mentioning
confidence: 99%